(untitled) (Journal of actual problems of jurisprudence, 2016)
With the development of national land legislation increasing the role of research the problem of property rights to land . Problems of property law acting as the object of this study based on civil law. Property rights to land primarily opredelyaetsya right as owner of the land in the land pravootnosheniy. Scientific identified signs of proprietary rights on the ground. Based on the analysis defined the concept of property rights to land.